(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Gridhrasi is the most common Vatavyadhi and pain is the main symptom which is explained as radiating from Sphik Pradesha and radiates downwards to Kati, Prusta, Uru, Janu, Jangha and Pada in which the patient is unable to walk properly. On the basis of symptoms of Gridhrasi given in classics, it can be correlated to Sciatica. It occurs due to spinal nerve irritation and is characterized by pain in the course of Sciatic nerve. It is estimated that Intervertebral disc prolapse is considered as the most common cause causing Sciatica. There are many treatment modalities mentioned in Ayurveda for the effective management of Gridhrasi. Among those treatments, Agnikarma is considered to be a treatment which gives immediate result in the management of pain. In current study a humble attempt is made to evaluate the role of Sarjarasa and Panchaloha Shalaka as Dahanopakarana in the pain management in Gridhrasi wsr to sciatica. Aim: To evaluate and compare the effect of Sarjarasa and Panchalohashalaka as Dahanopakarana, in the pain management in Gridhrasi wsr to Sciatica. Materials and Methods: Subjects for the study were taken from the OPD of department of Shalya tantra, Sri Sri College of Ayurvedic Science and Research Hospital, Bengaluru. The subjects who fulfill the criteria were registered randomly into two groups. Agnikarma were done with Panchaloha shalaka for the patients in group A, and Agnikarma were done with Sarjarasa for the patients in group B. Agnikarma were performed in the tenderest points for 4 sittings leaving a gap of 7 days. Patients were evaluated on the basis of objective and subjective criteria. Results: There is an overall improvement of 61.05% in Group A and 53% improvement in Group B. Conclusion: Patients in Group A got better result in parameters like SLR, Braggards, Lasegues test, Ruk and Spandana. Patients in Group B got better result in Toda and almost equal result is noticed in Sthambha. Both Dahanopakaranas shows significant improvement in all the parameters.